Risk assessment models for venous thromboembolism in pregnancy and in the puerperium: a systematic review. Issue 10 (12th October 2022) - Pandor, Abdullah; Daru, Jahnavi; Hunt, Beverley J; Rooney, Gill; Hamilton, Jean; Clowes, Mark; Goodacre, Steve; Nelson-Piercy, Catherine; Davis, Sarah
Abstract : Objectives: To assess the comparative accuracy of risk assessment models (RAMs) to identify women during pregnancy and the early postnatal period who are at increased risk of venous thromboembolism (VTE). Design: Systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data sources: MEDLINE, Embase, Cochrane Library and two research registers were searched until February 2021. Eligibility criteria: All validation studies that examined the accuracy of a multivariable RAM (or scoring system) for predicting the risk of developing VTE in women who are pregnant or in the puerperium (within 6 weeks post-delivery). Data extraction and synthesis: Two authors independently selected and extracted data. Risk of bias was appraised using PROBAST (Prediction model Risk Of Bias ASsessment Tool). Data were synthesised without meta-analysis. Results: Seventeen studies, comprising 19 externally validated RAMs and 1 internally validated model, met the inclusion criteria. The most widely evaluated RAMs were the Royal College of Obstetricians and Gynaecologists guidelines (six studies), American College of Obstetricians and Gynecologists guidelines (two studies), Swedish Society of Obstetrics and Gynecology guidelines (two studies) and the Lyon score (two studies). In general, estimates of sensitivity and specificity were highly variable with sensitivity estimates ranging from 0% to 100% for RAMs that were applied to antepartum women to predict antepartum or postpartum VTE and 0% to 100% for RAMs applied postpartum to predict postpartum VTE. Specificity estimates were similarly diverse ranging from 28% to 98% and 5% to 100%, respectively. Conclusions: Available data suggest that external validation studies have weak designs and limited generalisability, so estimates of prognostic accuracy are very uncertain. PROSPERO registration number: CRD42020221094.